Property-level adaptation to pluvial flooding: An analysis of individual behaviour and risk communication material - Lisa Dillenardt; Philip Bubeck; Paul Hudson; Bianca Wutzler; Annegret H. Thieken (Mitigation and Adaptation Strategies for Global Change, 2024)
Abstract Integrated risk management requires all stakeholders to work together proactively. Residents of floodplains can participate by implementing property-level adaptive measures. Risk communication materials can motivate those households to do so. Research on these materials is limited. Therefore, we systematically assessed freely available German risk communication materials in terms of their recommendations and how their content aligns with behavioural theories. We compare these results with data from surveyed households affected by urban flooding ( N 0.167em=0.167em1,352) on their attitudes towards flood adaptation and the adaptation measures implemented. 209 risk communication materials were reviewed. Adaptation options (mostly evasion or resistance strategies) were communicated in 93%, the hazard itself in 78%, the local hazard situation in 48%, and responsibilities in risk management in 54% of the risk communication materials. These aspects were rarely broken down for the reader by, for example, presenting the damage that can be expected or by presenting measures with the expected costs or their response efficacy. However, these details commonly increase the adaptive behaviour of residents according to commonly used behavioural theories. Survey data indicated that households feel able (82%) and responsible (41%) for implementing adaptive measures. However, many households indicated that measures are not effective (41%), too expensive (34%), and that there are not enough support programs (87%). We recommend that future risk communication materials focus more on communicating the efficacy and costs of adaptive measures and highlight funding opportunities. Our mixed method approach highlighted mismatches in information needed and provided.
Keywords: 330; Risk communication materials; Pluvial flooding; Adaptive behaviour; Household survey